2019
DOI: 10.1007/s12237-019-00661-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioextractive Removal of Nitrogen by Oysters in Great Bay Piscataqua River Estuary, New Hampshire, USA

Abstract: Eutrophication is a challenge to coastal waters around the globe. In many places, nutrient reductions from land-based sources have not been sufficient to achieve desired water quality improvements. Bivalve shellfish have shown promise as an in-water strategy to complement land-based nutrient management. A local-scale production model was used to estimate oyster (Crassostrea virginica) harvest and bioextraction of nitrogen (N) in Great Bay Piscataqua River Estuary (GBP), New Hampshire, USA, because a system-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 55 publications
(85 reference statements)
4
26
0
Order By: Relevance
“…The multiple simulations with differing mortalities at Site 1 also afforded us an opportunity to evaluate the accuracy of the FARM model at predicting harvest. Although previous studies have shown that the FARM model estimates harvest of cultivated oyster and other bivalves reasonably well (Ferreira et al 2009, Bricker et al 2020, it would be useful to have reported harvest at all Maryland farm study sites for confirmation of that for the Chesapeake Bay calibrated FARM model. The Maryland industry is young and growing, and there was only one site for which harvest numbers were made available for comparison with model results.…”
Section: Comparison Of Farm Production and N Removal Results To Reportedmentioning
confidence: 93%
See 4 more Smart Citations
“…The multiple simulations with differing mortalities at Site 1 also afforded us an opportunity to evaluate the accuracy of the FARM model at predicting harvest. Although previous studies have shown that the FARM model estimates harvest of cultivated oyster and other bivalves reasonably well (Ferreira et al 2009, Bricker et al 2020, it would be useful to have reported harvest at all Maryland farm study sites for confirmation of that for the Chesapeake Bay calibrated FARM model. The Maryland industry is young and growing, and there was only one site for which harvest numbers were made available for comparison with model results.…”
Section: Comparison Of Farm Production and N Removal Results To Reportedmentioning
confidence: 93%
“…Maryland Chesapeake Bay (this study) 1.78-25 28-457 Great Bay Piscataqua River Estuary (Bricker et al 2020) 0.57-5.27 37-101 Long Island Sound (Bricker et al 2018) 5.96 125 Multinational study* (Rose et al 2015) 1.18-8.70 51-345…”
Section: Locationmentioning
confidence: 85%
See 3 more Smart Citations